Enteroparasitoses in schools of the municipal public network (Research, Society and Development, 2019)
Parasitism refers to an association between the parasite and the host with a loss in the association. The objective of the present study was to evaluate the presence of enteroparasitoses in students of the municipal public network. The study was carried out in municipal schools in urban and peri-urban areas. Analyzes of the presence of enteroparasitoses in the feces of the students were performed by the method of Hoffman Pons & Janer. By means of the analyzes it was observed that 55% of the children investigated had at least one parasite in the organism, in which the main species found was Ascaris lumbricoides. Regarding the location of the school, students from peri-urban schools had a higher percentage of parasitism than those from schools located in urban areas. Evaluating the epidemiological aspects for the presence of intestinal parasites, it was verified that the students have the habit of consuming raw foods and walking barefoot. It is concluded that the majority of the students evaluated in the study were parasitized, this fact can be directly related to the hygienic habits of the students.